2019
DOI: 10.1111/1475-6773.13222
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how discrimination can affect health

Abstract: Background To provide an overview of the empirical research linking self‐reports of racial discrimination to health status and health service utilization. Methods A review of literature reviews and meta‐analyses published from January 2013 to 2019 was conducted using PubMed, PsycINFO, Sociological Abstracts, and Web of Science. Articles were considered for inclusion using the Preferred Reporting Items for Systematic Review and Meta‐Analyses (PRISMA) framework. Results Twenty‐nine studies met the criteria for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
398
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(450 citation statements)
references
References 72 publications
10
398
0
5
Order By: Relevance
“…However, lifetime experiences remain valid measures of discrimination, as discriminatory experiences may have long-term effects on behavior or health. 3,[11][12][13][14] Third, we note that many forms of discrimination, including sexual harassment and violence, are often under-reported-particularly on surveys administered by an interviewer, such as in this study. 35 Prior research has also found that women are often reluctant to label offensive experiences as "harassment."…”
Section: Limitationsmentioning
confidence: 81%
See 3 more Smart Citations
“…However, lifetime experiences remain valid measures of discrimination, as discriminatory experiences may have long-term effects on behavior or health. 3,[11][12][13][14] Third, we note that many forms of discrimination, including sexual harassment and violence, are often under-reported-particularly on surveys administered by an interviewer, such as in this study. 35 Prior research has also found that women are often reluctant to label offensive experiences as "harassment."…”
Section: Limitationsmentioning
confidence: 81%
“…[7][8][9] Evidence about the health impact of gender discrimination is supported indirectly by literature documenting the relationship between racial/ethnic discrimination and negative health outcomes. [10][11][12][13][14] These studies suggest that the experience of discrimination-be it institutional (eg, health care) or interpersonal (eg, microaggressions)-increases the body's stress response over time, and that discrimination is linked to a range of poor health-related behaviors, mental health outcomes, and physical health problems, including high blood pressure, heart disease, and mortality. [10][11][12][13][14] Experiencing gender discrimination may negatively impact women's health through parallel mechanisms, that is, through both psychological and physiological stress responses and health behaviors that lead to worse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An article by David Williams in this issue, as well as other prior research, has shown that major patterns of racism, sexism, and other discrimination can significantly harm the health and well-being of impacted populations and that self-reported discrimination is associated with worse health outcomes. [1][2][3][19][20][21][22][23][24]29 The Discrimination in the United States survey and the articles based on it extend prior work in this area by focusing on people's reports of their own and their family members' direct life experiences, rather than general perceptions of discrimination on the country; and by bringing together simultaneously these reported experiences across six groups, most of them underrepresented in much of public opinion research due to their low incidence in the population.…”
Section: Con Clus Ionsmentioning
confidence: 99%